Assessment Of Capacity Antagonist Of An Antimicrobial Produced By Streptomyces Sp Cepa 13a-2 Front Resistant Microorganisms Β-Lactam Hospital Waste - Lino-Navarro, Mirko (2016)
Objective. To evaluate the in vitro antimicrobial activity of marine actinomycete strain 13A-2 against enterobacteria producing P-lactamases isolated from patients with urinary tract infections. Material and Methods. Using the technique of double layer actinomycete is selected with the highest antagonistic activity against 16 Enterobacteriaceae Klebsiella sp., Proteus sp. and E. coli, beta-lactamase-producing patients with urinary infection Maternal Perinatal Institute of Lima. The strain 13-A2, isolated from a marine sponge collected from the Peruvian coast, was identified molecularly by amplification of the gene encoding 16S rRNA the peptidic nature of the antimicrobial was determined by techniques Bradford, Qubit fluoremeter, SDS-PAGE and HPLC. It managed to quantify the production of antimicrobial using a new culture medium proposed by the author which was compared with marine broth.